Research on the Knittability of Metallic Yarns in the Warp-knitted Mesh of a Deployable Antenna - Haiyan, Xu; Nanliang, Chen; Jinhua, Jiang (Fibres & textiles in Eastern Europe, 2023)
Metallic yarns are difficult to be knitted. To resolve the problem, the paper used the knitted yarn strength utilization factor to quantitatively characterize knittability, which was the ratio of yarn strength after being knitted to that of the original yarns. Furthermore, the relationship between the yarns' basic mechanical properties and the knitted yarn strength utilization factor was investigated by testing the yarns' basic mechanical properties. The results showed that it was feasible to quantitatively characterize the yarns' knittability using the knitted yarn strength utilization factor. And also the breaking strength of yarn was not correlated with the knittability. The elongation at break of the yarn was positively correlated with knittability. The bending stiffness of the yarn was negatively correlated with the knittability. Finally, a multiple linear regression model of the knittability and the mechanical properties of the yarn was developed. The model showed that there was a significant linear relationship between knittability and the elongation of yarns at break and the bending rigidity of yarns, with the bending stiffness of yarns being more significant.